2021
DOI: 10.3390/agriculture11030209
|View full text |Cite
|
Sign up to set email alerts
|

Organic Farming Increases the Technical Efficiency of Olive Farms in Italy

Abstract: While there is growing recognition of the positive role played by organic farming in the reduction of the negative externalities due to conventional agriculture, there is uncertainty about the effect of the latter on the economic performance of the farms. In this scenario, the present paper aims at investigating the effect of organic farming on technical efficiency in Italian olive farms. A cross-section dataset was analyzed through the stochastic frontier function, where the adoption of organic farming was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 87 publications
3
21
1
Order By: Relevance
“…The stochastic production frontier was initially developed by Aigner et al [31] and has underpinned most applied for farm productivity performance work (e.g., [32][33][34][35][36][37][38][39]). The specification of the stochastic frontier production function allows for the decomposition of the error term into a nonnegative random variable (U i ), associated with the technical inefficiency of the ith farm, as well as the Gaussian error term (V i ), which represents random variation in output due to factors beyond farmers' control, such as variation in weather patterns, measurement error, or any unspecified input variable.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…The stochastic production frontier was initially developed by Aigner et al [31] and has underpinned most applied for farm productivity performance work (e.g., [32][33][34][35][36][37][38][39]). The specification of the stochastic frontier production function allows for the decomposition of the error term into a nonnegative random variable (U i ), associated with the technical inefficiency of the ith farm, as well as the Gaussian error term (V i ), which represents random variation in output due to factors beyond farmers' control, such as variation in weather patterns, measurement error, or any unspecified input variable.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…Owing to the farm conditions in the arid area of northwest China-namely sufficient sunlight, heat, and scarce water resourcestwo modes of agriculture, irrigated agriculture and rain-fed agriculture, coexist. Therefore, assisting farmers to learn dry farming and water-saving techniques, including water and fertilizer integration under film drip irrigation and other practical techniques, and to understand pest and disease prevention and control technology, will assist in significantly improving the efficiency and level of agricultural production [59,60]. According to our investigations and studies, in recent years, villages and towns in Zhangye have used methods such as on-site guidance on production technology problems, centralized training in towns, demonstration of new technologies, and household training to provide practical technical training to farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature about contract farming is inconclusive regarding its potential role in smallholder farmers' upgradation. Many studies reported that contract farming is an institutional arrangement used to improve smallholder farmers' market access by providing agricultural raw materials to improve TE [5][6][7][8]. Research studies note that smallholder farmers participate in contract farming to reduce the risk associated with production to processors and put the subject cost burden-i.e., seed, pesticides, and fertilizer-on the processor and/or exporters [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Research studies note that smallholder farmers participate in contract farming to reduce the risk associated with production to processors and put the subject cost burden-i.e., seed, pesticides, and fertilizer-on the processor and/or exporters [9,10]. According to recent studies [5][6][7][8], contract farming offers farmers higher productivity and increases their market access. Likewise, Mishra et al [11] reported that contract farming might be a plausible solution to improve TE and help remove constraints along with production and marketing and ensure the supply of crop inputs, information, and capital to farmers.…”
Section: Introductionmentioning
confidence: 99%